ANALISIS DETERMINAN TAX AVOIDANCE PADA PERUSAHAAN SEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2018-2022 - Ningsih, Rischa Surya; Handayani, Desi; Ramadhea Jr, Syafira (Jurnal Riset Akuntansi Politala, 2024)
This study will look at how business age, size, profitability, and sales growth affect tax avoidance in the property and real estate sector firms listed on the Indonesia Stock Exchange (IDX) in the years 2018 through 2022. The population of the research consisted of all companies in the real estate and property industries that were listed on IDX between 2018 and 2022. The sample for this inquiry was gathered through intentional sampling. Based on the predefined criteria, 43 firms qualified, resulting in 215 data being collected, which served as the sample for this study. Websites for connected companies and the IDX were used as data sources. To examine the impact of each variable on tax evasion, the data was processed using the SPSS v.26 programme and analysed using multiple regression models. The findings indicated that a company's age, size, profitability, and rate of sales growth all had an impact on tax avoidance. Profitability and corporate size have some influence on tax avoidance. Despite the fact that firm age and sales growth have little bearing on tax avoidance.